2003
DOI: 10.1007/s00464-002-8855-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome and health-related quality of life after laparoscopic and open colectomy for benign disease

Abstract: LC was not different from OC for selected indications that measure long-term outcome and HRQL. SF-36 appears to be an appropriate instrument to measure postoperative HRQL, showing responsiveness to changes in objective outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 13 publications
2
41
0
Order By: Relevance
“…This is even more true if we consider the different type of surgery for DD [22]. This result confirmed with a highly discriminative questionnaire that there is no difference in terms of long-term HRQL between open and minimally invasive colonic resection as reported by Seitz et al and by Thaler et al [18,19]. In fact, even in term of generic quality of life (analyzed with the Italian version of CGQL) no significant differences were observed between patients treated with minimally invasive colonic resection and those treated with open surgery.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is even more true if we consider the different type of surgery for DD [22]. This result confirmed with a highly discriminative questionnaire that there is no difference in terms of long-term HRQL between open and minimally invasive colonic resection as reported by Seitz et al and by Thaler et al [18,19]. In fact, even in term of generic quality of life (analyzed with the Italian version of CGQL) no significant differences were observed between patients treated with minimally invasive colonic resection and those treated with open surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, advances in minimally invasive colonic surgery have broadened the spectrum of indications, and a large multicentric study has recently shown that 87% of the patients undergoing this procedure are affected with an uncomplicated DD [16]. Furthermore, although a prospective study showed significant improvement in quality of life and social functioning after laparoscopic sigmoid colectomy, others failed to identify any clear differences between laparoscopic sigmoid colectomy and open sigmoid colectomy in terms of quality of life [17][18][19]. Therefore, the impact and the possible role of minimally invasive colonic resection on DD management still appear unclear.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In minimally invasive surgery alone, it has been used to describe health-related quality of life following laparoscopic cholecystectomy (33), Nissen fundoplication (34), inguinal hernia repair (35), colectomy (36) and gastric bypass (37). In the field of LLDN, Perry et al showed that patients had reached population norms in all eight SF-36 domains by 6 to 12 months (38), but this was the first study to use the SF-36 to describe the recovery process within weeks following the procedure.…”
Section: Standardized Outcomesmentioning
confidence: 99%
“…Similarly, a variety of clinical studies observed comparable or even fewer wound healing complications after CO 2 laparoscopy in comparison with open surgery [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%